Optimizing brief, focused assessment of priority symptoms and concerns in recurrent and/or metastatic squamous cell carcinoma of the head and neck: Content validation of the Functional Assessment of Cancer Therapy/National Comprehensive Cancer Network Head and Neck Symptom Index‐10 (FHNSI‐10). Issue 4 (19th October 2021) - Shaunfield, Sara; Yount, Susan E; Boyken, Lara; Agulnik, Mark; Samant, Sandeep; Cella, David
Abstract: Background and Aims: Patients with recurrent and/or metastatic (R/M) squamous cell carcinoma of the head and neck (SCCHN) experience vast disease and treatment burdens. Brief, focused instruments are needed to assess patient‐reported priority symptoms and concerns as targeted outcome assessments for use in clinical research. Although the instrument was developed based on expert and patient input and is psychometrically valid, the Functional Assessment of Cancer Therapy (FACT)/National Comprehensive Cancer Network (NCCN) Head and Neck Symptom Index‐10 (FHNSI‐10) has yet to undergo content validation from the perspective of R/M SCCHN patients to evaluate its use as a brief symptom‐focused targeted endpoint assessment for use in clinical research. Methods: Interviews conducted with R/M SCCHN patients explored priority symptoms and concerns, followed by cognitive debriefing of the FHNSI‐10 to evaluate face validity. Transcripts were analyzed, and results were mapped to the FHNSI‐10. In accordance with published recommendations, expert input from the original development and published literature was considered for content validity assessment. Results: A total of 18 patients participated in a concept elicitation interview; saturation was obtained at interview 17. Most (83%) were undergoing active treatment, male (94%), white (72%), and did not have a college degree (67%). The most commonly mentioned symptoms were lumps/swelling, pain, sore throat, difficulty swallowing, and voice changes. For all items, ≥75% reported each question was relevant to their R/M SCCHN experience and 94% reported the instrument captured their experiences with R/M SCCHN. Conclusion: Results provide support for the content validity of the FHNSI‐10, inasmuch as all 10 items were spontaneously reported and considered relevant to R/M SCCHN. Content validity might be enhanced by adding cough and hearing impairment items; however, the existing FHNSI‐10 covers the majority of symptoms uncovered in interviews with a small sample of R/M SCCHN patients.